2000
DOI: 10.4049/jimmunol.164.4.1663
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Lipoxins Rapidly Stimulate Nonphlogistic Phagocytosis of Apoptotic Neutrophils by Monocyte-Derived Macrophages

Abstract: Lipoxins (LX) are lipoxygenase-derived eicosanoids generated during inflammation. LX inhibit polymorphonuclear neutrophil (PMN) chemotaxis and adhesion and are putative braking signals for PMN-mediated tissue injury. In this study, we report that LXA4 promotes another important step in the resolution phase of inflammation, namely, phagocytosis of apoptotic PMN by monocyte-derived macrophages (Mφ). LXA4 triggered rapid, concentration-dependent uptake of apoptotic PMN. This bioactivity was shared by stable synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
496
0
7

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 573 publications
(516 citation statements)
references
References 32 publications
(39 reference statements)
13
496
0
7
Order By: Relevance
“…42,43 Furthermore, recognition of apoptotic neutrophils exerts additional anti-inflammatory effects because it leads back to inhibit the release of pro-inflammatory mediators and activate the production of anti-inflammatory IL-10 and TGF-␤. 44 -46 Many proinflammatory mediators, such as annexin A1, glucocorticoid, and lipoxin A 4 , have been shown to produce proefferocytic effects, [47][48][49] but no data are available with respect to MC receptor agonists. Using plate-based and validated in vivo protocols, 23,24 we observed that AP214 evoked a marked increase in the phagocytosis of human apoptotic neutrophils by cultured macrophages in vitro (with an increment of ϳ70%) and resident peritoneal macrophages in vivo (30%).…”
Section: Discussionmentioning
confidence: 99%
“…42,43 Furthermore, recognition of apoptotic neutrophils exerts additional anti-inflammatory effects because it leads back to inhibit the release of pro-inflammatory mediators and activate the production of anti-inflammatory IL-10 and TGF-␤. 44 -46 Many proinflammatory mediators, such as annexin A1, glucocorticoid, and lipoxin A 4 , have been shown to produce proefferocytic effects, [47][48][49] but no data are available with respect to MC receptor agonists. Using plate-based and validated in vivo protocols, 23,24 we observed that AP214 evoked a marked increase in the phagocytosis of human apoptotic neutrophils by cultured macrophages in vitro (with an increment of ϳ70%) and resident peritoneal macrophages in vivo (30%).…”
Section: Discussionmentioning
confidence: 99%
“…Four distinct chemical families have been identified and named lipoxins, resolvins, protectins, and maresins. These families are biosynthesized in acute inflammation and control the duration and magnitude of inflammation via activation of mononuclear phagocyte recruitment, uptake of apoptotic neutrophils by the phagocytes, endogenous antimicrobial defense mechanisms, and clearance on mucosal surfaces [132][133][134][135][136][137][138]. An additional modulator for tissue repair and remodeling in the CNS injury is arginase-1.…”
Section: Inflammation Versus Resolutionmentioning
confidence: 99%
“…To assess the functional receptor that mediates the apoptosis suppressing action of SAA, we used Boc2 (27). Preincubation of PMN with Boc2 attenuated the effects of SAA on PMN viability and annexin V staining by 80 -97% (Fig.…”
Section: Saa Prolongs Neutrophil Survival By Delaying Apoptosis Throumentioning
confidence: 99%
“…22) and suppress IL-8 secretion (25). Annexin-1 accelerates PMN apoptosis (26), whereas LXA 4 /15-epi-LXA 4 does not affect PMN apoptosis (25,27). Thus, activation of ALX may result in potent proinflammatory or anti-inflammatory responses in a ligand-specific fashion.…”
mentioning
confidence: 99%